A contrastive analysis of syntactic structures employed in describing trends in English and Vietnamese business articles = Phân tích đối chiếu cấu trúc ngữ pháp dùng trong mô tả chiều hướng trong các bài báo thương mại tiếng Anh và tiếng Việt. M.A Thesis - Phạm, Thị Hà Trang (ĐHNN, 2017)
This research is directed to accomplish three goals: To investigate the syntactic structures used in describing trends in English and in Vietnamese from the perspective of traditional grammar. To make a contrastive analysis between English and Vietnamese syntactic structures used in describing trends in business articles to deduce their differences and similarities.To propose some pedagogical implications for better teaching and learning of describing charts or graphs and some recommendations for more effective translation works